PERAN PEMANASAN DAN PENDINGINAN YANG BENAR DALAM UPAYA PENCEGAHAN CEDERA PADA ATLET BULU TANGKIS PEMULA - Nimrot manalu; Uci Velda Zai; Samuel Sikettang; Apri Ebrata Purba; Yerikho Zai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Badminton is a sport characterized by dynamic movements, including rapid positional changes, jumps, sudden turns, and powerful racket swings. Beginning athletes often experience injuries due to a lack of understanding of preparation and recovery before and after training. This study aims to determine the role and effectiveness of proper warm-up and cool-down procedures in reducing the risk of injury in beginning badminton athletes. The research method used was descriptive qualitative through a review of scientific literature, field observations, and structured interviews with coaches and athletes. The results showed that systematic implementation of warm-up and cool-down procedures can reduce the incidence of injuries by up to 52%. Warm-ups increase muscle temperature, tissue elasticity, and blood flow, while cool-downs accelerate the elimination of metabolic waste and prevent muscle stiffness. It was concluded that implementing these two stages is the most effective, safe, and inexpensive primary preventative measure to be implemented from the beginning of an athlete's development.